TRANSFORMING ENGLISH LEARNING: DEVELOPING INTERACTIVE MEDIA GROUNDED IN PROBLEM-BASED LEARNING - Dalimunthe, Aghna Elfiana; Ampera, Dina; Simbolon, Naeklan (UNDIKMA, 2025)
This research aims to develop interactive learning media based on the Problem-Based Learning (PBL) model to improve English learning outcomes, particularly in reading comprehension of recount texts. The study employs a Research and Development (R&D) approach using the ADDIE model, which includes analysis, design, development, implementation, and evaluation. The product was developed using Canva and integrated with tools such as Quizizz, FlipHTML5, and Google Forms to create an engaging and student-centered learning experience. Validation was conducted by content, media, and instructional design experts, who rated the product as highly feasible. Implementation trials, including individual, small group, and field testing, indicated that the media was very practical and well-received by students. Effectiveness was assessed through a quasi-experimental design involving pre-tests and post-tests in control and experimental groups. The results showed a significant improvement in the experimental group’s performance, supported by a mean N-Gain score of 0.5845. The findings suggest that the developed media not only enhances learning outcomes but also promotes active, independent, and meaningful learning. The research contributes to digital learning innovation by offering a practical and effective instructional tool that aligns with 21st-century education goals.